3D-model and 3D-modeling in industrial design - Verhunov, S.V. (Pedagogy of Higher and Secondary Education, 2009)
In the article undertake the attempt to formulate the definition of 3D-model and process of 3D-modeling in industrial design, cons hit definitive aspects of this conception from the position of industrial designer and todays production process.